The Effect of Subjectivity in Incentives on the Performance Mediated by Knowledge Sharing Behavior - Klemensia Erna Christina Sinaga; R. A. Supriyono (The Indonesian Journal of Accounting Research, 2022)
This study examines the effect of subjectivity in incentives on the performance mediated by knowledge-sharing behavior. This research uses an experimental method by using students of the Faculty of Economics and Business at a state-owned university in Indonesia as the respondents. This study hypothesizes that managers' performance will affect subjectivity in incentives mediated by knowledge-sharing behavior. The results show that managers' performance is higher for the group of managers with subjectivity in incentives than those without incentive subjectivity. There is the role of knowledge-sharing behavior as a mediating variable. The findings of this research expand the research in managerial accounting, particularly on performance, subjectivity in incentives, and knowledge-sharing behavior. This research develops previous studies by incorporating the knowledge-sharing behavior variable as a mediating variable and influencing performance as a dependent variable. This research can help implement appropriate incentive systems for measuring performance and provide evidence on the importance of including knowledge-sharing behavior in reviewing employees’ formal performance, especially in accounting consulting services. In addition, this research will increase the companies’ awareness of building a work climate by incorporating a culture of knowledge sharing.